2018
DOI: 10.3390/ijerph15061193
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Shrubland and Grassland Soil Erodibility on the Loess Plateau

Abstract: Soil erosion is one of the most severe problems facing environments and has increased throughout the 20th century. Soil erodibility (K-factor) is one of the important indicators of land degradation, and many models have been used to estimate K values. Although soil erodibility has been estimated, the comparison of different models and their usage at a regional scale and, in particular, for different land use types, need more research. Four of the most widely distributed land use types were selected to analyze,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 96 publications
(131 reference statements)
4
18
0
Order By: Relevance
“…This result implies that the abandoned farmlands covered by shrubs, especially korshinsk peashrub, were the most effective restoration strategies to reduce soil erodibility on the Loess Plateau. The current result is supported by the result of Zhang et al (2018), who found that the soil erodibility in runoff plots covered by shrubs was less than that from plots covered by grass in the Ansai County of the Loess Plateau. The current result is supported by the result of Zhang et al (2018), who found that the soil erodibility in runoff plots covered by shrubs was less than that from plots covered by grass in the Ansai County of the Loess Plateau.…”
Section: Factors Influencing Soil Erodibilitysupporting
confidence: 79%
See 1 more Smart Citation
“…This result implies that the abandoned farmlands covered by shrubs, especially korshinsk peashrub, were the most effective restoration strategies to reduce soil erodibility on the Loess Plateau. The current result is supported by the result of Zhang et al (2018), who found that the soil erodibility in runoff plots covered by shrubs was less than that from plots covered by grass in the Ansai County of the Loess Plateau. The current result is supported by the result of Zhang et al (2018), who found that the soil erodibility in runoff plots covered by shrubs was less than that from plots covered by grass in the Ansai County of the Loess Plateau.…”
Section: Factors Influencing Soil Erodibilitysupporting
confidence: 79%
“…The variation in soil erodibility reflected by CSEI could be explained by the changes in BSC thickness, BD, OM, LD, and RD driven by vegetation restoration (Table V). The current result is supported by the result of Zhang et al (2018), who found that the soil erodibility in runoff plots covered by shrubs was less than that from plots covered by grass in the Ansai County of the Loess Plateau.…”
Section: Effect Of Vegetation Restoration Strategies On the Comprehensupporting
confidence: 79%
“…Coarse soil texture means large and more numerous soil pores, which benefits downward transport of fine particle in the process of surface water infiltration [42,43]. Soil particle organic matters easily combine with fine particles to form organic-inorganic complexes or soil aggregates, which reduces the moving ability of clay and silt [12,13]. Low SOC content in the soils of the JRC restricts the protection ability to fine particle, thus the possibility of soil erosion depends on soil particle size distribution, i.e., K factor is mainly affected by soil texture.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological processes mainly include stress processes and protection processes in this study. The ecological stress process in the loess hilly and gully region mainly focused on non-point source pollution and soil erosion in agricultural areas [6,39,49]. According to the proportion of the cultivated land area of the watershed, combined with the total application amount of fertilizer, the fertilizer application intensity was calculated.…”
Section: Target Layer Criterion Layer Index Layer Weightmentioning
confidence: 99%